Can small non-peptide motilin agonists force a breakthrough as gastroprokinetic drugs? - Depoortere, Inge (Blackwell Publishing Ltd, 2012)
GSK962040 is a small selective motilin receptor agonist currently under investigation in clinical trials for the treatment of conditions associated with delayed gastric emptying. As reported in this issue of the British Journal of Pharmacology, Broad et al., studied for the first time the region-dependent contractile effects of motilin and GSK962040 in human smooth muscle strips. Both compounds facilitated cholinergically mediated contractions of human gastric antral muscle strips at low concentrations and induced smooth muscle contractions at high concentrations. The effect was less pronounced in the fundus and almost absent in the colon. The long-lasting facilitation of cholinergic responses in the antrum by GSK962040 compared with the fading responses to motilin may be of importance from a clinical point of view. The approach used by Broad et al. with human tissue is a validated model to identify motilin receptor agonists with therapeutic value. LINKED ARTICLE: This article is a commentary on Broad et al., pp. 763–774 of this issue. To view this paper visit http://dx.doi.org/10.1111/j.1476-5381.2012.02009.x